2016
DOI: 10.1039/c6nr05002f
|View full text |Cite
|
Sign up to set email alerts
|

CuGaS2–ZnS p–n nanoheterostructures: a promising visible light photo-catalyst for water-splitting hydrogen production

Abstract: In this work, novel CuGaS-ZnS p-n type semiconductor nanoheterostructures were synthesized by a solution route, and demonstrated experimentally to be a very promising visible light active photo-catalyst for water-splitting hydrogen production. The construction of CuGaS-ZnS heterostructures follows a multi-step strategy, employing CuS nanocrystals first as catalytic assistants for the hetero-growth of ZnS on their surfaces, and then as sacrificial seeds for the formation of CuGaS. Excitingly, attributed to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 51 publications
0
42
0
1
Order By: Relevance
“…Considering the toxicity and photocorrosion of CdS, others tried to replace CdS with nontoxic and robust semiconductors with suitable band structures. Zhao et al reported a thermal reaction method for the fabrication of matchstick‐like CuGaS 2 and ZnS p–n heterojunction . Due to the efficient charge separation and transfer process, the p–n heterojunction system showed 15 times higher catalytic performance than pure CuGaS 2 under visible light.…”
Section: Applicationsmentioning
confidence: 99%
“…Considering the toxicity and photocorrosion of CdS, others tried to replace CdS with nontoxic and robust semiconductors with suitable band structures. Zhao et al reported a thermal reaction method for the fabrication of matchstick‐like CuGaS 2 and ZnS p–n heterojunction . Due to the efficient charge separation and transfer process, the p–n heterojunction system showed 15 times higher catalytic performance than pure CuGaS 2 under visible light.…”
Section: Applicationsmentioning
confidence: 99%
“…For example, restricting to CuGaS 2 , there are reports of at least 8 different variations on the common dot, platelet, and rod shapes, starting from Cu 2-X S seeds. [21][22][23][24][25][26] This combination of compositional and morphological diversity suggests that the Cu 2-X S system may be ideal for tailoring Figure 1. Transmission Electron Microscopy (TEM) images of CuGaS 2 NR growth from aliquots taken at 0 s, 30 s, 1 min, 2 min, and 5 min.…”
Section: Introductionmentioning
confidence: 99%
“…Cu-based ternary semiconductor nanocrystals are of great scientific interest for applications in solar cells (Rivest et al, 2011), light-emitting devices (LEDs) (Yoon et al, 2019;Li et al, 2020), biological imaging (Meng et al, 2017), photo-catalytic (Zhao et al, 2016), photoelectric detectors because of their low-toxicity, tunable band gaps, and high absorption coefficients (Pejova et al, 2020). Especially, ternary nanocrystals based on Cu 1.94 S, with localized surface plasmon resonance due to the large number of copper vacancies, have been widely demonstrated for photoelectrochemical water reduction and solar cells due to their high concentration of free charge carriers (Liu et al, 2017;Bai et al, 2020;Bera et al, 2020;Zhu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%